Barrier-free tourism: Criteria and rational objects choice for inclusive tour - Victoria S. PLOTNIKOVA; Olga D. AFONINA (Zenodo, 2022)
The article is devoted to the analysis of the availability of the tourist infrastructure objects in the Republic of Karelia for their compliance with the requirements of a barrier-free environment. A barrier-free environment is especially relevant for disabled people (DP). Several problems in this area are related to the accessibility of tourist facilities for disabled people, and the lack of adapted tourism products. This requires solving specific problems at the level of the state, regional local authorities, entrepreneurs, and citizens. This work presents an overview of the definition of the "barrier-free tourism" concept, the main problems of this type of tourism, which are associated with transport, medical control, special tourist equipment, the operation of hotels, and information support. The quality criteria for improving the barrier-free environment were also determined, which are achieved while maintaining the accessibility, safety, convenience and information content of buildings for the needs of the disabled and other people with limited mobility without infringing on the relevant rights and opportunities of other people. Based on the systematization of factors that have the most impact on the development of barrier-free tourism and the selected criteria, a study was conducted on the availability of tourist facilities in the Republic of Karelia. The study was based on the analysis of sites of tourist objects, reviews of visitors with disabilities and visits to these objects for the purpose of personal observation and study of the availability for different groups of visitors. The result of the work was an inclusive tour that can be used in the practical activities of tourism enterprises. Originally published in https://ruservices.rgutspubl.org/index.php/1/article/view/19